AB0938 Clinical features and prevalence of psoriatic arthritis in patients with cutaneous psoriasis referred from the primary care. (23rd January 2014) - Fernandez-Sueiro, J.L.; Pértega Diaz, S.; Pinto Tasende, J.; González, E.; Fernández Lopez, J.; Oreiro, N.; de Toro, F.; Blanco, F.
Abstract : Background: The prevalence of psoriatic arthritis in patients with psoriasis goes from 6-42%, these differences may be due to the studied population, the definition of the disease and the estimation based on questionnaires. Objectives: To estimate the prevalence of PsA in patients with cutaneous psoriasis referred from the primary care Methods: Cross sectional study evaluating patients referred from the primary care with a diagnosis of cutaneous psoriasis without arthritis. Patients were evaluated in the following way: personal and family history, criteria for IBP, spinal and peripheral pain (VAS), peripheral joint count: tender and swollen (78/76), metrology (cervical rotation (CR), occiput to wall distance (OW), lateral lumbar flexion (LLF), modified Schober (mS)). MASES. SF12, DLQI, PASI, BSA. Peripheral and axial x-rays. ESR, CRP, anti CCP and HLA-B27. Case definition was made according to clinical judgement. A descriptive analysis of the variables was performed. Results: 122 patients were studied. The medium age was 53, 06±16, 42 years. 57, 4% were female, time of psoriasis duration was 23, 4±15, 1 years. 72, 1% had type I psoriasis. 29, 8% nail involvement, 1, 6% dactylitis. IBP 12, 3%. Nocturnal and overall spinal pain past week 1, 76±2, 88 and 2, 13±3, 04, peripheral VAS 2, 65±3, 3. TJC 0, 57±3, 11, SJC 0, 01±0, 09. mS 4, 46±0, 89, OW 0, 11±0, 85, LLF 16, 25±3, 99, CR <70°: 5%, enthesitis 10, 7%, PASI 0, 21±0, 98, BSA <10%: 95, 9%, DLQI 1, 64±2, 55 SF12 physical 50±8, 7, SF12 mental 45, 5±11, 3, ESR ≤20 72, 1%, CRP <0, 8: 83% anti-CCP ≤25: 97, 2%. Negative FR: 90, 1%. Negative HLA-B27: 90, 3%. Peripheral erosions: 19%, at least grade II unilateral sacroiliitis: 15, 5%. According to clinical criteria 12 patients had PsA 9, 8% (95%IC: 4, 1%–15, 5%). These patients had: nail involvement: 25%, dactylitis 8, 3%. Nocturnal and overall spinal pain past week 3, 25±3, 57 and 4, 17±3, 35, peripheral VAS 6, 33±3, 31, TJC 4, 50±9, 04, SJC 0, 00, mS 4, 48±1, 03, OW 0, 00, LLF 14, 92±4, 42. CR <70°: 8, 3%, enthesitis 41, 7%, PASI 0, 33±1, 15, BSA <10%: 100%, DLQI 1, 42±1, 56 SF12 physical 43, 09±11, 39, SF12 mental 39, 28±12, 11, ESR ≤20 70%, CRP <0, 8: 80%, anti-CCP ≤25: 100%. Negative FR 91, 7%. Negative HLA-B27 91, 7%. Peripheral erosions 18, 2%, sacroiliitis grade II unilateral or higher 45, 5% Conclusions: In this cross sectional study applying clinical judgment as gold standard for the diagnosis of PsA, the prevalence of PsA in patients with cutaneous psoriasis referred from the primary care was of 9, 8%. Funded with a grant from: Instituto de Salud Carlos III, FIS PI080789 Disclosure of Interest: None Declared